Increasing Student Speaking Capability by Using Substitution and Convert Drills at State Senior High School Number 5 Kota Jambi - A Rasyid Ali (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The aim of this research is to investigate and to know about the strategy of learning speaking in English teaching, because there are many problems on teaching English, namely facility, method, media, and competency of teacher, capability of teacher, willingness of teacher, management of head Master, commitment of teacher, and discipline of teacher and student’s competency. All the problems that previous above are very influence of English teaching quality, on particularly Learning Speaking, that is why the writer   ( researcher ) eager to express of sharing idea,  what happen on teaching and learning English, especially on Learning  Speaking. Various strategies is very important  on each teaching in order student does not feel bore to follow on learning English, Specially on Speaking, therefore in this opportunity the  researcher  introduce  the strategy that used  which is entitled “ Substitution and Convert  Drills“.